Development of Cardiorespiratory Fitness in Children in the Transition From Kindergarten to Basic School According to Participation in Organized Sports - Järvamägi, Merike; Riso, Eva-Maria; Reisberg, Kirkke; Jürimäe, Jaak (Frontiers in Physiology, 2022)
Purpose: This study examined the development of cardiorespiratory fitness (CRF) in children in the transition from kindergarten to basic school according to participation in organized sports and estimated the associations of CRF and body composition indices during the transition from childhood to preadolescence. Methods: Children participated in the three-staged study (kindergarten, 6.6 years, n = 212; 1st grade, 7.6 years, n = 136; and 5th grade, 11.5 years, n = 142) for 5 years and were categorized into three groups according to their participation in organized sports in the study period (whole period, episodically, and never). Cardiorespiratory fitness was assessed by performing a 20-m shuttle run test, while body composition was measured by skinfold thicknesses, and physical activity was registered with an accelerometer. International gender- and age-specific CRF reference normativities were also used to characterize the participants. Results: Children who participated consistently in organized sports had significantly higher CRF levels and lower body fatness (31.3 ± 13.5 laps in 20 m shuttle run; 21.1% ± 6.3% body fat) in 11.5 years than in children who had never participated in sports clubs (20.7 ± 12.0 laps in 20-m shuttle run; 26.1% ± 6.8% body fat). Body composition and CRF did not associate in consistently trained children. The proportion of 5th grade children demonstrating age-appropriate healthy CRF was almost threefold higher in the group of consistent sports training among both boys and girls than among non-members of sports clubs. Conclusion: Consistent attendance in organized sports in childhood and early preadolescence ensures higher CRF and healthier body composition than in children who had no experience of organized sports.